1991
DOI: 10.1093/nar/19.24.6737
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and characterization of therad4gene ofSchizosaccharomyces pombe; a gene showing short regions of sequence similarity to the human XRCC1 gene

Abstract: The rad4.116 mutant of the fission yeast Schizosaccharomyces pombe is temperature-sensitive for growth, as well as being sensitive to the killing actions of both ultraviolet light and ionizing radiation. We have cloned the rad4 gene by complementation of the temperature sensitive phenotype of the rad4.116 mutant with a S. pombe gene bank. The rad4 gene fully complemented the UV sensitivity of the rad4.116 mutant. The gene is predicted to encode a protein of 579 amino acids with a basic tail, a possible zinc fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0

Year Published

1994
1994
2010
2010

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(37 citation statements)
references
References 22 publications
2
35
0
Order By: Relevance
“…Fission yeast has a single ortholog of each of Dpb11, Sld2, and Sld3, all of which are essential for chromosome replication (Fenech et al 1991;Nakajima and Masukata 2002;Noguchi et al 2002). Sld3 can associate with origins in the absence of CDK activity as in budding yeast, and is required for the subsequent recruitment of GINS and Cdc45 (Yabuuchi et al 2006).…”
Section: Sld2 and Sld3 Are The Major Targets For Cdk During The Initimentioning
confidence: 99%
“…Fission yeast has a single ortholog of each of Dpb11, Sld2, and Sld3, all of which are essential for chromosome replication (Fenech et al 1991;Nakajima and Masukata 2002;Noguchi et al 2002). Sld3 can associate with origins in the absence of CDK activity as in budding yeast, and is required for the subsequent recruitment of GINS and Cdc45 (Yabuuchi et al 2006).…”
Section: Sld2 and Sld3 Are The Major Targets For Cdk During The Initimentioning
confidence: 99%
“…TopBPl possessed eight repeating regions (regions 1 -8) similar to regions 1 and 2 of Rad4 protein (Fig. 3A), which repairs DNA damage by ultraviolet and radiation [13]. Rad4 is identical to Cut5, which is required for the onset of S phase and for the restraint of M phase before the completion of S phase [14].…”
Section: Sequence Of Topbplmentioning
confidence: 99%
“…Gene cloning of the cut5+ gene indicated that it was identical to the rad4+ gene previously reported by Fenech et al (1991). The rad4+ gene is one of many rad+ genes identified in fission yeast and is known to be required for the repair of X-ray-and UV-damaged DNA.…”
Section: Cell Division Block Produced By Uv Irradiationmentioning
confidence: 54%
“…The cut5+ gene encodes a putative 74 kDa (designated p74) polypeptide (Fenech et al, 1991;Saka and Yanagida, 1993;Lehmann, 1993). Close sequence alignment indicates that the protein product consists of four distinct domains: two repeti tive domains and two hydrophilic domains (Fig.…”
Section: The Product Of the Cut5+ Gene Is Similar To An Oncoproteinmentioning
confidence: 99%
See 1 more Smart Citation